Planning to Design a Railway Network System: Using a Simulation Model - Ali, A. J. Adham; Mohamed, Younis (2015)
The railway is one of the most popular means of a mass transportation system. The proposed approach has a universal character and can be applied by city and authorities to design a strategic plan of urban transportation systems to solve an advanced transportation problem. This study is focused to design a new railway network between two big cities in Malaysia which are Kuala Lumpur and Kuantan. The Simulation model applied for planning a new railway design and analysis are the important factors. The overall objective of this approach is to increase the passenger service and public transportation system benefit, as well as to make available other transportation categories between these cities. In addition, the model will choose the best railway network that can get more passengers among the urbanization between these two cities.